Gingival ossifying myopericytoma in a pediatric patient: Immunohistochemical analysis and literature review. (August 2020) - Almeida, Lana Kei Yamamoto; Jabur, Roberto Oliveira; Silveira, Heitor Albergoni; Polanco, Xiomara Beatriz Jimenez; da Silva, Raquel Assed Bezerra; Ribeiro-Silva, Alfredo; León, Jorge Esquiche
Highlights: Myopericytoma should be included in the differential diagnosis of gingival nodules. Approximately 25% of oral myopericytomas can occur in pediatric patients. Conservative surgery is the treatment of choice, with good prognosis. Abstract: Myopericytoma is a rare mesenchymal tumor characterized by a hemangiopericytoma-like vascular pattern with perivascular myoid differentiation. To date, only 11 cases of oral myopericytoma have been reported. To the best of our knowledge, myopericytoma with gingival involvement and associated with calcifications has not been reported, expanding their clinicopathological spectrum. Herein, we report a 12-year-old girl female patient who presented a gingival nodule diagnosed as ossifying myopericytoma, which should be considered in the differential diagnosis when assessing oral soft tissue lesions, especially in pediatric patients.